Auer rod-like inclusions in multiple myeloma - Metzgeroth, Georgia; Back, W.; Maywald, O.; Schatz, M.; Willer, Andreas; Hehlmann, Rüdiger; Hastka, Jan (Annals of hematology, 2003)
We report a case of IgA multiple myeloma, in which the plasma cells showed multiple azurophilic, Auer rod-like intracytoplasmic inclusions in May-Grünwald-Giemsa-stained marrow smears. Cytochemical stainings revealed a strong α-N-esterase activity of these inclusions, whereas the reactions for peroxidase, Sudan black, chloroacetate esterase, and PAS were negative. Immunostaining verified IgA-kappa inside the plasma cells. The inclusions, however, were negative. Amyloid and lysozyme were also not detectable. Electron microscopy showed Auer rod-like inclusions with a smooth surface in the neighborhood of a well-developed rough endoplasmic reticulum, but with no direct relation to it. The inclusions showed a fine lamellar substructure, and the periodicity of the filamentous striations was about 10 nm, comparable with the substructure of typical Auer rods. Our findings suggest that the azurophilic inclusions in multiple myeloma are Auer rod-related structures, which likewise consist of active lysosomal enzymes. In contrast to the Auer rods in acute myeloblastic leukemia (AML), however, the inclusions in multiple myeloma consist of typical plasma cell enzymes.
Published online: 14 December 2002
Gesehen am 16.05.2022